Ladina social activism in Guatemala City, 1871-1954 - Harms, Patricia (University of New Mexico Press, 2020)
In this groundbreaking new study on ladinas in Guatemala City, Patricia Harms contests the virtual erasure of women from the country's national memory and its historical consciousness.